Proinflammatory Effects of Ubiquitin-Specific Protease 5 (USP5) in Rheumatoid Arthritis Fibroblast-Like Synoviocytes - Xiao-Bo Luo; Jian-Cheng Xi; Zhen Liu; Yu Long; Li-tao Li; Zhan-Peng Luo; Dao-Hong Liu (Hindawi Limited, 2020)
Rheumatoid arthritis (RA) is a worldwide chronic autoimmune inflammatory disease which is affecting approximately 1% of the total population. It is characterized by abnormal proliferation of fibroblast-like synoviocytes (FLS) and increased production of proinflammatory cytokines. In the current study, we were aiming to investigate the role of ubiquitin-specific protease 5 (USP5) in the inflammatory process in RA-FLS. Expression of USP5 was found upregulated in RA-FLS compared with that in osteoarthritis- (OA-) FLS, and IL-1β stimulation increased USP5 expression in a time-dependent manner. Furthermore, we found that USP5 overexpression significantly aggravated proinflammatory cytokine production and related nuclear factor κB (NF-κB) signaling activation. Consistently, silencing of USP5 decreased the release of cytokines and inhibited the activation of NF-κB. In addition, USP5 was found to interact with tumor necrosis factor receptor-associated factor 6 (TRAF6) and remove its K48-linked polyubiquitination chains therefore stabilizing TRAF6. Our data showed that a USP5-positive cell regulates inflammatory processes in RA-FLS and suggested USP5 as a potential target for RA treatment.